DNA BARCODE KERANG KEPAH (Polymesoda Sp.) DI BAGAN PERCUT DAN DANAU SIOMBAK SUMATERA UTARA MENGGUNAKAN GEN CYTOCHROME OXIDASE SUB UNIT 1 (CO1) - Utami, Mutiara Alya; Idami, Zahratul; Manalu, Kartika (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2025)
Background: DNA Barcode is a molecular technique using short sequences of nucleotide bases that aims to identify and classify living things. This study aims to obtain nucleotide characters from DNA barcode results from kepah clams using CO1 genes in Sumatran waters, to determine the results of molecular identification of species of kepah clams (Polymesoda sp.) found in North Sumatra waters, and to determine the kinship relationships of kepah clam species (Polymesoda sp.) in North Sumatra waters. Samples were obtained in Bagan Percut and Lake Siombak, carried out from July to August 2023 at the Biomolecular Laboratory, Medan State University. Methods: The method used is to use DNA barcodes with CO1 genes. Results: The results of research of species of the genus Polymesoda sp. namely Polymesoda erosa and Polymesoda expansa obtained from processing sequencing data by analyzing nucleotide characters using the Mega 11 application, namely variations in the percentage of AT content (62.69%), GC content (37.56%) for Polymesoda erosa species and AT content (62.42%), GC content (38.64%) for Polymesoda expansa species, which means both species have primitive properties. Molecular identification of the genus Polymesoda sp. obtained from the results of DNA sequence samples along 369 bp so that it is suitable to be used as DNA barcodes. The genetic distance between the species studied is Polymesoda erosa (0.000) and Polymesoda expansa (0.920) which means they have a close genetic distance. Conclusion: Phylogenetic tree reconstruction carried out using the Neighbour Joining method shows that between the two species Polymesoda erosa (Bagan Percut) and Polymesoda expansa (Lake Siombak) have a close kinship and come from a common ancestor.